The Influence of Full Day School Policy on Islamic Religious Education Learning in Elementary Schools - Dahlan, Alwi; Azmi, Ela Fadila; Zuraidah, Yeni; Hambali, Usnan (Yayasan Rahmat Islamiyah, 2025)
The Full Day School policy has been implemented in various elementary schools to enhance learning effectiveness, including in Islamic Religious Education (PAI) subjects. This study aims to analyze the influence of the Full Day School policy on PAI learning in elementary schools, focusing on effectiveness, student engagement, and understanding of religious concepts. The research employs a qualitative approach with data collection techniques including observation, interviews, and documentation. The findings indicate that the Full Day School policy positively impacts the duration of PAI learning but also presents challenges such as student fatigue and the need for more varied teaching methods. The study highlights the importance of innovative teaching strategies and flexible approaches to ensure that PAI learning remains effective and engaging for students.